Problems of implementing the classification of expenditures of the state budget of Ukraine (Economics and region, 2019)
The classification of budget expenditures is extremely important for the implementation of the state budget, in compliance with the principles inherent in this stage in general and the principles of efficiency and economy in particular. The importance of implementing a proper budget classification is obvious, as it will allow you to successfully manage budget expenditures and maximize the impact of the tasks that the state is facing. Considering the extremely important role of the classification of expenditures for the effective organization of budget execution in the expenditure part, the author examines the changes in the approaches to the classification of expenditures of the state budget from 1917 to the times of independence of our state, and also analyzes changes in them during the times of sovereign Ukraine. The attention is paid to the positive and negative features of the budget classification, enshrined in the Budget Code of Ukraine, and a comparative analysis of the interpretation of the state budget expenditures by scholars – lawyers and economists. It is suggested own vision in this paper.
Keywords: expenditures; classification; program classification; departmental classification; economic classification; functional classification